S and B microalloying of biodegradable Fe-30Mn-1C - Effects on microstructure, tensile properties, in vitro degradation and cytotoxicity. (15th March 2018) - Hufenbach, J.; Kochta, F.; Wendrock, H.; Voß, A.; Giebeler, L.; Oswald, S.; Pilz, S.; Kühn, U.; Lode, A.; Gelinsky, M.; Gebert, A.
Abstract: Austenitic Fe-Mn-C-based alloys are considered as promising candidates for biodegradable vascular implants due to their high strength, ductility and mechanical integrity during degradation. The present study demonstrates that microalloying with S and B is an effective method to further enhance the degradation rate and the mechanical properties of a Fe-30Mn-1C twinning-induced plasticity (TWIP) alloy without deteriorating the biocompatibility. For studying the microstructural changes due to S or B addition, the alloys were analysed by X-ray diffraction (XRD) as well as scanning electron microscopy (SEM) in combination with energy-dispersive X-ray spectroscopy (EDX), wavelength dispersive X-ray analysis (WDX) and electron backscatter diffraction (EBSD). Thereby precipitates of (Fe0.3 Mn0.7 )S and (Fe, Mn)23 (C3 B3 ) types were detected in the austenitic matrix. These precipitates have a distinct influence not only on the mechanical properties under tensile load but also on the occurring corrosion mechanism. This was displayed by potentiodynamic polarization measurements and immersion tests in simulated body fluid (SBF) and associated SEM as well as X-ray photoelectron spectroscopy (XPS) investigations. In vitro cytotoxicity analyses with L929 fibroblast cells indicated that microalloying with S and B does not affect the cytocompatibility. Thus, the novel alloy modifications show a high potential for future application as biodegradable implant material. Graphical abstract: Image 1 Highlights: Fine-grained Fe-Mn-C(-B/S) TWIP alloys were processed by fast solidification. Microalloying of Fe-30Mn-1C with S or B results in the precipitation of (Fe0.3 Mn0.7 )S or (Fe, Mn)23 (C3 B3 ), respectively, in the austenitic matrix. S and B addition is an effective method to enhance the degradation rate and the mechanical properties of biodegradable Fe-30Mn-1C. Significantly higher yield and ultimate tensile strength compared to 316L steel and Fe-30Mn. Especially Fe-30Mn-1C-0.025S shows a high potential for future application as biodegradable vascular implant material.